2014
DOI: 10.1590/198053142771
|View full text |Cite
|
Sign up to set email alerts
|

Turnos e segregação escolar: discutindo as desigualdades intraescolares

Abstract: The paper analyzes patterns of intra-and interschool

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
0
4
1
2
Order By: Relevance
“…Um último elemento estudado na cidade do Rio de Janeiro, que possivelmente está presente em outras redes de ensino em países em desenvolvimento, com população ainda jovem, é a alocação de alunos de forma não aleatória entre turnos escolares (Bartholo e Costa, 2014). Foi observado até 2014 que 90% das escolas apresentavam dois turnos de ensino, manhã e tarde.…”
Section: Segregação Escolar No Brasil: O Que Já Sabemos?unclassified
See 1 more Smart Citation
“…Um último elemento estudado na cidade do Rio de Janeiro, que possivelmente está presente em outras redes de ensino em países em desenvolvimento, com população ainda jovem, é a alocação de alunos de forma não aleatória entre turnos escolares (Bartholo e Costa, 2014). Foi observado até 2014 que 90% das escolas apresentavam dois turnos de ensino, manhã e tarde.…”
Section: Segregação Escolar No Brasil: O Que Já Sabemos?unclassified
“…Os pesquisadores fizeram uma análise comparando a segregação escolar considerando a alocação nos turnos e comparando com contra factual que desconsiderava os turnos. A alocação dos alunos nos turnos aumentava de forma importante os níveis de segregação no sistema sugerindo uma alocação não aleatória (Bartholo e Costa, 2014).…”
Section: Segregação Escolar No Brasil: O Que Já Sabemos?unclassified
“…In reality, what characterizes the "shift policy" is the absence of any regulation regarding the allocation of pupils. Bartholo and Costa (2014) has shown that the allocation of potentially disadvantaged pupils across "school shifts" is far from being a random distribution. The author used the Dissimilarity Index (D) (Duncan;Duncan, 1955) and the Segregation Index (GS) (GORARD; TAYLOR; FITZ, 2003) to capture the "net effect" of the school "shift" allocation 8 .…”
Section: Tiago Bartholo E Marcio Da Costamentioning
confidence: 99%
“…The calculations where replicated throughout seven years to test for robustness. This is a clear example of legislation influencing the social composition of schools (Bartholo;Costa, 2014).…”
Section: Tiago Bartholo E Marcio Da Costamentioning
confidence: 99%
See 1 more Smart Citation